Análisis de señales de EEG para apoyar el diagnóstico de la enfermedad de Parkinson (EP), mediante características espectrales (2022)
Early diagnosis of Parkinson's disease is a challenge for today's society, because there is no specific test to determine the possible existence of PD, and it is currently not feasible to makea presymptomatic diagnosis of the disease in order to develop new treatments